US Antidumping Petitions and Revealed Comparative Advantage of Shrimp Exporting Countries - Chia-Lin Chang; Michael McAleer; Dang-Khoa Nguyen (Tinbergen Institute, 2016)
The paper explores the trade competitiveness of seven major shrimp exporting countries, namely Vietnam, China, Thailand, Ecuador, India, Indonesia and Mexico, to the USA. Specifically, we investigate whether the United States (US) antidumping petitions impact upon the bilateral revealed comparative advantage (RCA) indexes for each of the seven shrimp exporting countries with the USA. Monthly data from January 2003 to December 2014 and the panel data model are used to examine the determinants of the RCA for the shrimp exporting countries. The empirical results show the shrimp exporting countries have superior competitiveness against the shrimp market in the USA. Moreover, the RCA indexes are significantly negatively influenced by shrimp prices, and are positively affected by US income per capita. However, the EMS (Early Mortality Syndrome) shrimp disease, domestic US shrimp quantity, exchange rate, and US antidumping laws are found to have no significant impacts on the RCA indexes. In terms of policy implications, the USA should try to reduce production costs of shrimp in the US market instead of imposing antidumping petitions, and the shrimp exporting countries should maintain their comparative advantage and diversify into new markets.
Keywords: C23; F13; P45; Q17; 330; Shrimp; antidumping; revealed comparative advantage; panel data model